2012
DOI: 10.1134/s0965545x12060028
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of silica-filled polystyrene: From microcomposites to nanocomposites

Abstract: Rheology and viscoelastic behavior of polystyrene (PS)/silica microcomposites and nanocom posites were studied. The apparent viscosity, transient shear stress growth after startup shear flow and stress relaxation after cessation of flow at various shear rates, the complex dynamic viscosity, the storage and loss moduli at small and large strain amplitudes and various frequencies were performed. The effect of size, shape and volume concentration of silica was discussed. The maximum volume concentration, correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…This indicates that the behaviour of the composites at high frequencies was dominated by the binder system (matrix) and that the contribution of filler particles was less significant. Similar findings were reported for different highly filled composites; for example, SBR rubber and carbon-black and silica particles [44], polydimethylsiloxane (PDMS) and spherical glass beads [49], polyethylene terephthalate (PET) and ferrite nanoparticles [50], and PP and ceramic powder [51]. In the low-frequency region (below ≈10 rad/s) the flattening of the G curve and to a lesser extent also G" curve could be observed.…”
Section: Frequency Sweep Testsupporting
confidence: 84%
See 2 more Smart Citations
“…This indicates that the behaviour of the composites at high frequencies was dominated by the binder system (matrix) and that the contribution of filler particles was less significant. Similar findings were reported for different highly filled composites; for example, SBR rubber and carbon-black and silica particles [44], polydimethylsiloxane (PDMS) and spherical glass beads [49], polyethylene terephthalate (PET) and ferrite nanoparticles [50], and PP and ceramic powder [51]. In the low-frequency region (below ≈10 rad/s) the flattening of the G curve and to a lesser extent also G" curve could be observed.…”
Section: Frequency Sweep Testsupporting
confidence: 84%
“…This indicates that the behaviour of the composites at high frequencies was dominated by the binder system (matrix) and that the contribution of filler particles was less significant. Similar findings were reported for different highly filled composites; for example, SBR rubber and carbon-black and silica particles [44], polydimethylsiloxane (PDMS) and spherical glass beads [49], polyethylene The comparison of the frequency behaviour of composite materials at different loading levels (Figure 6) revealed that, as in the case of amplitude sweep tests, the viscoelastic behaviour in LVR depends on the type of filler material. However, in the case of 30 vol.% filler loading, there was no difference between dynamic behaviour (G and G") of Al and 316L material, respectively, in the whole frequency range studied.…”
Section: Frequency Sweep Testsupporting
confidence: 80%
See 1 more Smart Citation
“…Additionally, for higher particle concentrations, the viscosity can be predicted via the empirical Krieger–Dougherty equation ηr=1ϕϕm[]ηϕmwhere [η] is the intrinsic viscosity and φ m is the maximum loading. This equation has been used to fit experimental data for concentrated colloidal suspensions and composites with micron sized fillers . Both models predict an increase in viscosity with increasing filler loading.…”
Section: Introductionmentioning
confidence: 99%
“…In suspensions, size, size distribution, shape and volume fraction of the filler particles affect the flow properties [25]. Fumed silica is a widely used filler with particle sizes ranging from 5 to 50 nm [26,27] and it has been applied to modify, for example, the flow properties of polymers such as PDMS [28,29], PS [30], polyethyleneoxide (PEO) [31], polyethyleneglycol (PEG) [32], and polyethyleneterephtalate (PET) [33], as well as UV curable systems including carbodiimide diacrylate [34] and TE [35]. Due to their large surface area-to-weight ratio, nanoparticles can alter material properties at significantly smaller weight fractions than their micro-sized counterparts [30,31,36].…”
Section: Introductionmentioning
confidence: 99%